Fried green tomatoes at the Whistle Stop Cafe - Flagg, Fannie (Random House, 1987)
Evelyn Couch, a woman caught in the slump of middle age, gains a new outlook on life when she befriends eighty-year-old Ninny Threadgood who tells her the story of the Whistle Stop Cafe and the two women who ran it in the 1930s, best friends Idgie and Ruth.